The Role of the Sharia Supervisory Board in Sharia Insurance: Responsibilities and Functions - Mhd Ilham Nst; Mutya Fradilla Budiman; Dewi Lestari; Diah Sisca; Fara Nazla (ISNU Nine-Star Multidisciplinary Journal, 2025)
This study aims to examine the role, responsibilities, and functions of the Sharia Supervisory Board (SSB) in Islamic insurance. The SSB plays a strategic role in ensuring that all Islamic insurance operations and products comply with Islamic principles, as stipulated in fatwas and applicable regulations. The SSB's primary responsibilities include supervising, advising, and validating products and contracts used by Islamic insurance companies. This function encompasses oversight of the implementation of Islamic contracts such as mudharabah, wakalah, and tabarru', as well as periodic evaluation of Islamic compliance. Furthermore, the SSB is tasked with providing recommendations for system and policy improvements to minimize potential Islamic deviations. Using a qualitative descriptive approach, this study found that the SSB acts not only as a supervisor but also as a strategic partner in the development of innovative Islamic insurance products. The conclusion suggests that an active and competent SSB is key to maintaining Islamic integrity and customer trust in the Islamic insurance industry.